How to Support Learners in Developing Usable and Lasting Knowledge of STEM - Krajcik, Joe; Delen, Ibrahim (International Journal of Education in Mathematics, Science and Technology, 2016)
All students need to experience the joy of discovery and innovation. In this study we discussed how STEM education that focuses on design can provide students with these opportunities. Learning environments that focus on STEM questions and engage students in design have the potential help students learn core ideas related to STEM as well as engage students in the learning process. This study presents examples that can be used by educators and also focuses on how STEM learning environments can connect knowledge of scientific and engineering ideas with focusing on scientific and engineering practices.